Thermal denaturation of mesophilic and thermophilic 5S ribonucleic acids. - Varricchio, F (1976)
The Tm of Bacillus stearothermophilus 5S ribonucleic acid (RNA) is 1.5 +/- 0.5 C higher than that of 5S RNAs from B. subtilis and Escherichia coli. Melting in 50% methanol and in formaldehyde indicate that both base stacking and helical regions are involved in the slightly increased thermal stability of B. stearothermophilus 5S RNA. It is probable that the 5S RNA makes only a minor contribution to the thermostability of B. stearothermophilus 50S ribosomal subunits.